Pasto in the context of the formation of the Republic of Gran Colombia (1821-1831) - Chaves Martinez, Ingrid Viviana (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This article intends to analyse the exercise and the configuration of power relationships in the city of Pasto, taking into consideration its social structure. In this study, the following topics are approached: the characteristics of the city’s social structure, hierarchized by criteria related to ethnic and class origin, and the economic characteristics marked by a period of crisis, given the duration of the war and fiscal repression, imposed by the new governmental order. The study was conducted based on social history, which allows us to see the changes, analyse the form of organization and the economic implications in the society of the time. All this allows for a better understanding of the origin of the political and administrative changes that took place in the city of Pasto, during its incorporation to the republican political project.